Diné teachings and public health students informing peers and relatives about vaccine education: Providing Diné (Navajo)-centered COVID-19 education materials using student health messengers - Tutt, Marissa; Begay, Chassity; George, Shawndeena; Dickerson, Christopher; Kahn, Carmella; Bauer, Mark; Teufel-Shone, Nicolette (Frontiers in Public Health, 2022)
Introduction/Background: On April 9, 2021, the Centers for Disease Control and Prevention (CDC) reported only 19.9% of United States (US) adults were fully vaccinated against COVID-19. In that same week, the Navajo Nation (NN) reported 37.4% of residents were fully vaccinated making the NN a leader in the uptake of COVID-19 vaccines. Despite high vaccination rates, vaccine hesitancy exists within the NN. The Diné (Navajo) Teachings and Public Health Students Informing Peers and Relatives about Vaccine Education (RAVE) intervention was designed to utilize trusted health messengers as an effective means to address adults’ vaccine concerns and hesitancy. Methods: The research team used COVID-19 vaccine materials developed in a previous collaboration with non-Navajo tribal communities and publicly available materials. Diné Traditional Knowledge Holders (TKHs) were interviewed to develop and incorporate Diné specific information on individual and collective health behaviors into the RAVE materials. These drafted health education materials were presented to NN community health representatives (CHRs) and Diné public health students using a consensus panel approach. NN residents who participated in the intervention completed a 16-element retrospective pretest. Results: The adaptation and tailoring process of materials yielded 4 health education materials. The students recruited 46 adults for health education sessions. These participants then completed the retrospective pretest. Changes in the 16 elements were in the desired direction though only six were significant: four related to attitudes and two concerned vaccination intention. Participants were more likely to consider vaccination and to try to get vaccinated after the education session. Discussion: Trusted messengers and culturally centered materials have been identified as effective means of health behavior education with Native American audiences. RAVE applied these intervention elements by 1) training Diné College public health students to leverage their cultural knowledge and social relationships (cultural and social capital) to recruit vaccine hesitant adults and provide education; 2) building on previous understanding of Native American communities’ vaccine concerns; and 3) integrating Diné perspectives on individual and collective health into the adaptation of materials designed for general audiences; this knowledge was gained from interviews with TKHs.